CD40 promotes MHC class II expression on adipose tissue macrophages and regulates adipose tissue CD4(+) T cells with obesity - Morris, David L. (J Leukoc Biol, 2016)
Obesity activates both innate and adaptive immune responses in adipose tissue, but the mechanisms critical for regulating these responses remain unknown. CD40/CD40L signaling provides bidirectional costimulatory signals between antigen-presenting cells and CD4(+) T cells, and CD40L expression is increased in obese humans. Therefore, we examined the contribution of CD40 to the progression of obesity-induced inflammation in mice. CD40 was highly expressed on adipose tissue macrophages in mice, and CD40/CD40L signaling promoted the expression of antigen-presenting cell markers in adipose tissue macrophages. When fed a high fat diet, Cd40-deficient mice had reduced accumulation of conventional CD4(+) T cells (T(conv): CD3(+)CD4(+)Foxp3(−)) in visceral fat compared with wild-type mice. By contrast, the number of regulatory CD4(+) T cells (T(reg): CD3(+)CD4(+)Foxp3(+)) in lean and obese fat was similar between wild-type and knockout mice. Adipose tissue macrophage content and inflammatory gene expression in fat did not differ between obese wild-type and knockout mice; however, major histocompatibility complex class II and CD86 expression on adipose tissue macrophages was reduced in visceral fat from knockout mice. Similar results were observed in chimeric mice with hematopoietic Cd40-deficiency. Nonetheless, neither whole body nor hematopoietic disruption of CD40 ameliorated obesity-induced insulin resistance in mice. In human adipose tissue, CD40 expression was positively correlated with CD80 and CD86 expression in obese patients with type 2 diabetes. These findings indicate that CD40 signaling in adipose tissue macrophages regulates major histocompatibility complex class II and CD86 expression to control the expansion of CD4(+) T cells; however, this is largely dispensable for the development of obesity-induced inflammation and insulin resistance in mice.